A Compendium of Perspectives on Diabetes: A Challenge for Sustainable Health in the Modern Era - Verma, Amit K (Diabetes Metab Syndr Obes, 2021)
Diabetes is a chronic illness. Hyperglycemia is the characteristic of this disorder. Diabetes is a global crisis which affects the economy and health of all nations. Over the last decades, the number of individuals living with diabetes has significantly increased worldwide. Asia is a key epicenter of the emerging diabetes epidemic, with China and India the two nations having the highest number of diabetic people. Economic development, modernization, unhealthy diet, population aging, and sedentary lifestyles are the major factors responsible for the increasing diabetes epidemic. Diabetes is associated with several complications, and cardiovascular disease is the most important cause of morbidity and mortality among people with diabetes. These life-threatening problems can be prevented or delayed by proper management of diabetes. Lifestyle modification is an important factor to decrease the diabetes risk. The frequency of diabetic complications will rise if there is a lack of cost-effective and sustainable interventions. Hence, prevention of diabetes and its complications such as diabetic retinopathy and cardiovascular disease should be a crucial part of all future health-related public policies among all nations. This review summarizes current epidemiological aspects of diabetes in the world along with its complications, preventive measures, and treatment.